PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. TOBA PULP LESTARI, TBK MEDAN (KANTOR CABANG MEDAN) - MARKUS DODDY SIMANJUNTAK (LP2MTBM MAKARIOZ, 2020)
Human resources become the most important factor in an organization or company, the role of HR in the company isimplemented in the form of employee workforce. For this reason, human resources need to be developed and considered sothat the quality of these human resources can be improved, thus impacting on improving employee performance. This studyaims to determine the effect of organizational culture on employee performance at PT. Toba Pulp Lestari, Tbk Medan.This study uses questionnaires, interviews, and observations in the data collection methods needed to support this research.In this study the data analysis method used is a simple linear regression analysis to find out how big the role oforganizational culture is in improving employee performance.Based on the results of a simple linear regression analysis using the equation Y = 15,720 + 0.780 X, it is concluded that if thecompany creates the right organizational culture, it will be able to improve employee performance. Partial testing obtainedthe conclusion that organizational culture has a positive and significant effect on employee performance. Based on testingthe coefficient of determination used to determine the contribution of the independent variable (organizational culture) to thedependent variable (employee performance). So that the results obtained by using the R-Square of 60.8% independentvariables on the dependent variable while 39.2% derived from other factors not included in this study.